ANALISIS PORTOFOLIO KREDIT, RISIKO, DAN RETURN BANK UMUM KONVENSIONAL - Yosua Sopater Siregar; Apriani Dorkas Rambu Atahau; Imanuel Madea Sakti (Jurnal Manajemen, 2022)
This study aims to determine the credit portfolio strategy (focus or diversification strategy) based on the economic sector in conventional commercial banks grouped by business activity (BUKU) in the period January 2016 - December 2018 and analyze the effect of credit portfolio concentration and credit risk on rates of return. This study uses secondary data obtained from Indonesian Banking Statistics at the Financial Services Authority (OJK). This study used 4 samples, namely BUKU 1, BUKU 2, BUKU 3, BUKU 4. The results showed that the concentration of the credit portfolio had a positive effect on credit risk, while credit risk had a negative effect on return. In addition, the mediating role of the credit risk variable is not proven to affect the effect of the credit portfolio and credit risk. These results suggest that the credit portfolio concentration strategy in certain sector can increase credit risk so that it tends to reduce the rate of return. Thus, banks need to diversify their credit portfolios to minimize credit risk.